Towards Hierarchical Self-Optimization in Autonomous Groups of Mobile Robots - Rasche, Christoph; Jungmann, Alexander; Schierbaum, Thomas; Werdehausen, Benjamin; Kleinjohann, Bernd (IEEE 10th International Conference on Industrial Informatics,)

Hierarchical Hybrid Planning for a Self-Optimizing Active Suspension System - Esau, Natascha; Krüger, Martin; Rasche, Christoph; Beringer, Steffen; Kleinjohann, Lisa; Kleinjohann, Bernd (7th IEEE Conference in Industrial Electronics and Applications)
This paper presents a hierarchical hyprid planning approach developed for realizing self-optimizing mechatronic systems. The hybrid planning approach is based on a discrete plan and a forecast of continuous system behavior generated by simulation during runtime. This does not only allow an online adaptation of a previously generated plan with regard to the actual system state as well as the current environmental conditions, even the planning objectives may be adapted to newly arising needs during system operation. The planner exploits the hierarchy already present in the system model by considering hierarchical parameterizations of the system as a discrete dimension of choice. The parameterizations are proposed by a novel hierarchical multiobjective optimization, which calculates Pareto points in a bottom up fashion, taking into account the constraints imposed by lower levels of the system hierarchy on the higher ones. Evaluations of the hierarchical hybrid planner in the context of an innovative railbound transport system show that it outperforms its non-hierarchical predecessor.

Evaluating Quality of Online Image Registration of Aerial Images Using Virtual Forces - Stern, Claudius; Rasche, Christoph; Kleinjohann, Lisa; Kleinjohann, Bernd (Proceedings of The 16th International Conference on Image Processing, Computer Vision, & Pattern Recognition)

A First Step Towards Real-time Virtual Machine Migration in Heterogeneous Multi-Processor Systems - Grösbrink, Stefan (Symposium on System-integrated Intelligence)

Binary Mutation Testing Through Dynamic Translation - Becker, Markus; Kuznik, Christoph; Joy, M. tech. Mabel Mary; Xie, Tao; Müller, Wolfgang (42nd Annual IEEE/IFIP International Conference on Dependable Systems and Networks (DSN))

Enhanced Schedulability Analysis of Hard Real-Time Systems on Power Manageable Multi-Core Platforms - He, Da; Müller, Wolfgang (Third International Symposium on Advances in Embedded Systems and Applications (ESA-2012))

Compilation of Methodologies to Speed up the Verification Process at System Level - Radke, Stephan; Rülke, Steffen; Oliveira, Marcio F.; Kuznik, Christoph; Müller, Wolfgang; Ecker, Wolfgang; Esen, Volkan; Hufnagel, Simon; Bannow, Nico; Oetjens, Jan-Hendrik; Brazdrum, Helmut; Janssen, Peter; et al. (edaWorkshop 12)

Process integrated wire-bond quality control by means of cytokine-Formal Immune Networks - Montealegre, Norma; Hagenkötter, Sebastian (Journal of Intelligent Manufacturing 23(3))

Towards Adaptive Resource Management for Virtualized Real-Time Systems - Grösbrink, Stefan; Oberthür, Simon; Baldin, Daniel (4th Workshop on Adaptive and Reconfigurable Embedded Systems (CPSWeek 2012))

Online Model Checking for Dependable Real-time Systems - Zhao, Yuhong; Rammig, Franz-Josef (16th IEEE International Symposium on Object/Component/Service-Oriented Real-Time Distributed Computing-Shenzhen, China)

Agent-Based Modeling and Simulation of Artificial Immune Systems - Montealegre, Norma; Rammig, Franz-Josef (Third IEEE Workshop on Self-Organizing Real-Time Systems (SORT 2012))

Self-Coordination as Fundamental Concept for Cyber Physical Systems - Rammig, Franz-Josef (2nd SBC Workshop on Autonomic Distributed Systems - WoSiDA 2012)

Planarization of Geographic Cluster-based Overlay Graphs in Realistic Wireless Networks - Mathews, Emi (Ninth International Conference On Information Technology : New Generations (ITNG))

Online Energy-Efficient Hard Real-Time Scheduling for Component Oriented Systems - He, Da; Müller, Wolfgang (2012 IEEE 15th International Symposium on Object/Component/Service-Oriented Real-Time Distributed Computing (ISORC))

Efficient Alignment of Aerial Images Based on Virtual Forces - Stern, Claudius; Rasche, Christoph; Kleinjohann, Lisa; Kleinjohann, Bernd (Proceedings of The Eighth International Conference on Autonomic and Autonomous Systems (ICAS))
Getting a contemporary aerial overview of a disaster area is a foremost task in search and rescue operations. We previously have introduced a novel method for registering a large amount of aerial images when camera parameters are almost unknown and no reference images are available. This paper provides two new methods, which improve our method for image registration based on virtual forces. The goal is to improve the performance of creating a contemporary overview map of a disaster area assembling several images taken by unmanned aerial vehicles (UAVs) equipped with cameras. In this paper, two new methods are introduced: a method for rotation estimation and a method for scale estimation. Both methods use fast heuristic approximation approaches and statistical methods to provide high robustness. We discuss the methods in detail and compare them to our previous approach regarding robustness and calculation speed. We can show that the new methods significantly increase the performance of the image registration process.

Efficient Color-Based Image Segmentation and Feature Classification for Image Processing in Embedded Systems - Jungmann, Alexander; Kleinjohann, Bernd; Kleinjohann, Lisa; Bieshaar, Maarten (Proceedings of the 4th International Conference on Resource Intensive Applications and Services (INTENSIVE))
In this paper, a color based feature extraction and classification approach for image processing in embedded systems in presented. The algorithms and data structures developed for this approach pay particular attention to reduce memory consumption and computation power of the entire image processing, since embedded systems usually impose strong restrictions regarding those resources. The feature extraction is realized in terms of an image segmentation algorithm. The criteria of homogeneity for merging pixels and regions is provided by the color classification mechanism, which incorporates appropriate methods for defining, representing and accessing subspaces in the working color space. By doing so, pixels and regions with color values that belong to the same color class can be merged. Furthermore, pixels with redundant color values that do not belong to any pre-defined color class can be completely discarded in order to minimize computational effort. Subsequently, the extracted regions are converted to a more convenient feature representation in terms of statistical moments up to and including second order. For evaluation, the whole image processing approach is applied to a mobile representative of embedded systems within the scope of a simple real-world scenario.

Dynamic Resource Management for Virtualized Mixed-Criticality Systems - Grösbrink, Stefan; Oberthür, Simon; Baldin, Daniel (Quo Vadis, Virtual Platforms? (in conjunction with Design, Automation and Test in Europe DATE 2012))

A SystemC Library for Advanced TLM Verification - Oliveira, Marcio F.; Kuznik, Christoph; Müller, Wolfgang; Ecker, Wolfgang; Esen, Volkan (Proceeding of Design and Verification Conference (DVCON))

A model-driven engineering framework for embedded systems design - Nascimento, Francisco A. M.; Oliveira, Marcio F.; Wagner, Flavio (Innovations in Systems and Software Engineering 8)

MOUSSE: scaling MOdelling and verification to complex heterogeneoUS embedded Systems Evolution - Becker, Markus; Gnokam Defo, Gilles Bertrand; Müller, Wolfgang; Fummi, F.; Pravadelli, G.; Vinco, Sara (Design, Automation and Test in Europe (DATE 2012))